2014
DOI: 10.1039/c3nr06092f
|View full text |Cite
|
Sign up to set email alerts
|

Highly conductive and flexible polymer composites with improved mechanical and electromagnetic interference shielding performances

Abstract: New flexible and conductive materials (FCMs) comprising a quartz fiber cloth (QFC) reinforced multi-walled carbon nanotubes (MWCNTs)-carbon aerogel (QMCA) and poly(dimethylsiloxane) (PDMS) have been successfully prepared. The QMCA-PDMS composite with a very low loading of MWCNTs (∼1.6 wt%) demonstrates enhanced performance in tensile strength (129.6 MPa), modulus (3.41 GPa) and electromagnetic interference (EMI) shielding efficiency (SE) (∼16 dB in X-band (8.2-12.4 GHz) region). Compared to the QC (where MWCNT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
69
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(70 citation statements)
references
References 35 publications
1
69
0
Order By: Relevance
“…These particular subset of foams exhibit increased strength [1][2][3], electrical conductivities [2,4,5], and damping [6][7][8][9] over their traditional counterparts. While the applications of polymer nanocomposite foams like flexible sensors [10] and electromagnetic shielding [2,11] have been widely reported, very few studies have however focused on the damping applications for noise and vibration control. In recent years experimental studies and numerical modelling have been carried out to describe the widely reported interfacial sliding mechanism in nanocomposites for damping treatments.…”
Section: Introductionmentioning
confidence: 99%
“…These particular subset of foams exhibit increased strength [1][2][3], electrical conductivities [2,4,5], and damping [6][7][8][9] over their traditional counterparts. While the applications of polymer nanocomposite foams like flexible sensors [10] and electromagnetic shielding [2,11] have been widely reported, very few studies have however focused on the damping applications for noise and vibration control. In recent years experimental studies and numerical modelling have been carried out to describe the widely reported interfacial sliding mechanism in nanocomposites for damping treatments.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to high EMI shielding performance, light weight is an additional important technical requirement for potential applications especially in the areas of automobile and aerospace. Searching for the library of EMI shielding materials, conductive polymer composites foams [4,5], carbon foams [6] and conductive aerogels [7] emerged as potential EMI shielding materials due to their advantages in effective weight reduction, chemical stability and design flexibility. Electrical conductive fillers, such as carbon nanofibers (CNFs) [8,9], carbon nanotubes (CNTs) [10,11] and graphene sheets [12][13][14], were commonly used to form a conducting network with desirable electrical conductivity within the intrinsically insulating polymer foam matrix, a crucial requirement for effective EMI shielding properties.…”
Section: Introductionmentioning
confidence: 99%
“…Samples containing higher CNTs are more reflective as a consequence of a higher electrical conductivity. [43][44][45] Therefore, the sample that only contains graphene presents the highest P A which decreases as the CNT content is increased due to the higher amount of reflected power. The electromagnetic shielding mechanism was investigated through a shielding efficiency (SE) analysis (eqn (2), (3) and (4)).…”
Section: Electromagnetic Characterizationmentioning
confidence: 99%